(3TPhQ GdPgHs - (3GdCfUGQj, CHh GdMSf, GHf CQHY QCS, Ydj Hf ehSi Hf Ydj, J (B593 (3g`s ((3CHh HcQ YHO Gddg Hf YeQ Hf SjeGf GdMdHjs)
(3ChdgG (B:s
(3HSe Gddg EPG KdK GdeQjN HGdRgQI GeQD hbGQf HGdHOQ GdefjQ PcGQ hhGUd SYO GdeTJQi HYWGQ Edi RMd cj jSJajO VjGA MQa GdCdas
(3BNQgG (B:s
(3MQa GdjGA ; Cbhd dbhe fGgjG Mjf GYQVhG Yf GdPgH GdeMbb dh jaY Gdfgi , CdG dG JQhehG YdefG ef MLGQI EPG MejJ de jHO CSQGQgG GdMei Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\26s
(3cTa GdXfhf (B2\1029s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs